PEMBERIAN NAFKAH PEMELIHARAAN ANAK SEBAGAI AKIBAT PERCERAIAN DI KABUPATEN SLEMAN - Puji Wulandari (Jurnal Penelitian Humaniora, 2005)
Abstract This research aims at identifying anything used as Judge’s consideration in determining the amount of cost of child’s nursing after divorce and at identifying the effort taken when the husband in charge of the cost does not follow the decision. This research is juridical-normative, based on the library research to gain secondary data in low accompanied by field research. This research employs two kinds of data, primary data obtained from interview with resource person, and secondary data obtained from library research-by collecting and studying documents of primary, secondary, and tertiary materials of law. Then, the data were analyzed qualitatively. The following conclusions are dawn from the research findings, 1)based on Decree Number 560/Pdt.G/PA.Smn, the Judge’s consideration on determining the cost of child nursing after divorce is in line with Act Number 1 year 1974 regarding the Marriage and Compilation of Islamic Law (CIL). The Judge’s consideration are article 41(a) Act Number 1 year 1974 and article 156 CIL. Because the child is still underage, the father is in charge of child’s nursing cost. 2)attempts that can be made if the husband in charge of the problem disobeys the law are by bringing rekopensi and an agreement between the wife and the husband. If the husband still disobeys his obligation, the wife tends not to put the problem in court because it takes a long time and big money-not as worth as what are demanded. Keywords: divorce, provision of the cost